Daylight Design Graphs for Baghdad City Sky - Younis Mahmoud Saleem (Iraqi Journal of Architecture and Planning, 2018)
Baghdad city constitutes one of the areas have clear sky with complex and ununiformdistribution of light in the sky dome. This was one of the explanations why there is fewstudies concern with daylighting design in clear skies, from there, this research oriented todevise a new method that can assist in achieving the appropriate levels of lighting forinterior spaces. The aim of this research is tempted to find a method that can help designersin achieving the appropriate levels of daylight in architectural spaces with different formsand sizes.The annual distribution rate of daylight was calculated for the horizontal surfaces ofdifferent orientations and unobstructed horizontal surface Furthermore account the Intensityof sky light and sun light on vertical surfaces of building facades opposite to the windows.Been reached a number of Graphs as protractor used with architectural drawings(horizontal plans and vertical sections), and by adopting of such Graphs, designers canmeasure the levels of daylight in any points within the space.Applied this method on a number of design characteristics of shape and direct thewindow and measure its influence in enlightened points within the space as their distancechanges away from window. The research found a number of conclusions linked between thepredictability of the distribution of daylighting levels within the space and pattern ofdistribution of windows within its